Monitoring of solar panel simulator using Visual Studio - Alamsyah, M. Thoriq; Asnil (Journal of Industrial Automation and Electrical Engineering, 2025)
The use of solar panels as an alternative energy source is increasingly widespread due to their environmentally friendly nature. However, their efficiency is highly influenced by external factors such as temperature and light intensity. Therefore, a monitoring system capable of observing panel performance in real-time is required. This study designs and develops a solar panel simulator monitoring system based on the Arduino Uno microcontroller and a Visual Basic interface, which displays sensor data in both graphical and tabular forms. The sensors used include DHT22 (temperature), BH1750 (light intensity and irradiation), ACS712 (current), and a voltage divider (voltage). The system is tested using four solar panel circuit configurations: series, parallel, series-parallel, and total cross tied (TCT). The test results show that each configuration is highly dependent on light intensity in relation to the current and voltage produced. The data visualization using Visual Basic functions optimally and is consistent with measurement results, indicating that this system is effective for monitoring and analyzing the performance of solar panels under simulated conditions